The incidence of neurological symptoms after thrombolytic therapy in elderly patients with acute myocardial infarction - Hassan Shemirani; Seyyedeh Fatemeh Bahari Saravi; Maysam Khoshavi (ARYA Atherosclerosis, 2012)
BACKGROUND: Reperfusion therapy is the standard treatment of acute myocardial infarction (AMI). If the percutaneous coronary intervention (PCI), as a preferred reperfusion strategy, is not available, thrombolytic therapy would be chosen as an alternative treatment. However, the effect of thrombolytic therapy on old patients is still controversial especially due to its effects on increasing the incidence of intracranial hemorrhage (ICH). In this study, we evaluated the incidence of neurological symptoms and ICH after thrombolytic therapy in AMI patients over 65 years of age.    METHODS: A total number of 300 AMI patients over 65 years of age who referred to the hospital within 12 hours of their symptom onset and had no contraindications for receiving thrombolytic therapy were selected. The patients were admitted in Noor Hospital, Isfahan, Iran, between 2004 and 2006. All of them received streptokinase (SK) in the same way. Their information was extracted from their files and collected by a questionnaire.    RESULTS: Among 300 patients in our study, there were 124 women (41.33%) and 176 men (58.66%). Their mean age was 74 ± 9 years (range: 65-92 years). Moreover, 78% were discharged after one week of hospitalization and 22% (66 patients) died. Arrhythmias or myocardial reinfarction were the leading cause of death in 56.06% of all deaths. No death due to ICH and no evidence of ICH, such as hemiparesis or loss of consciousness, were observed.     CONCLUSION: We suggest that thrombolytic therapy in old patients with AMI is a good alternative treatment when there is no access to an equipped PCI facility. In our study, the increase in mortality rate due to ICH was not high enough to prevent us from prescribing SK for AMI patients over 65 years of age.   Keywords: Acute Myocardial Infarction, Percutaneous Coronary Intervention, Intracranial Hemorrhage, Streptokinase, Thrombolytic Therapy.